Energy economical and environmental analysis of industrial boilers using VSD - Atabani, A.E.; Saidur, Rahman; Silitonga, A.S.; Mahlia, T.M.I. (Applied Mechanics and Materials, 2012)
As a result of the successful implementation of the industrialization plan in 1985; Malaysia has changed from an agricultural economy into industrial based economy. The industrial sector represents the highest consuming sector across all other sectors and accounts for about 48 of all total energy demand. This paper is concerned with an energy saving, economic and environmental analysis of industrial boilers in Malaysia when using variable speed drives (VSD). The results obtained when reducing the speed of water pumps by 60 show that 4 GWh, 93.6 of energy, RM 863,375 and 2,160 ton of CO2 could be saved annually. These results represent high energy saving, environmental and economic benefits associated with this energy saving technology.